Medical and Dental Faculty’s Attitude towards E-Learning as the Mode of Teaching during Covid-19 Pandemic: Attitude towards E- Learning - Wahad Khan , Mahvish; Ibrahim , Saira; Zaigham , Abdul Mueed; Inayat, Naveed; Tirmazi , Sobia Masood; Munir, Nadia (Pakistan Journal of Health Sciences, 2023)
The use of modern technology infrastructure is regarded as critical for the successful adoption of innovative teaching approaches. Objective: To determine the attitudes and concerns of medical and dental faculty about the use of E-learning as a medium of instruction during the Covid-19 outbreak. Methods: This cross-sectional study included 368 faculty members from Medical and Dental Colleges of Punjab province was conducted utilizing a questionnaire developed following a thorough literature review and analysis of questionnaires from previous studies. A 5-point Likert scale was used to record knowledge, attitude, and practice, and the questionnaires were graded. SPSS version 22 was used to enter the data. The mean and SD of quantitative variables such as age and total score for knowledge, attitude, and practice score was calculated. Gender, education level, knowledge, attitude, and practice were all represented as frequency (%). Results: Zoom was shown to be the most commonly utilized software (69.0%). E-learning was deemed a beneficial tool in medical education by 56% of the respondents. An equal percentage of individuals (35%) agreed and disapproved the use of E-learning approaches over traditional ones. Only 30% participants resisted the change from traditional educational methods. Technological infrastructure was considered crucial for successful implementation of E-learning by 46% of the participants. Conclusion: Faculty members are using the available infrastructure to implement E-learning teaching modalities to the best of their knowledge and abilities.